Analiza segretja motorskega zaščitnega stikala pri trajni tokovni obremenitvi - Hrovat, Gorazd (Informacije MIDEM, 2003)
Nowadays, electrical motor is, due to its simplicity, robustness and immediate readiness to operate, the most wide-spread driving machine wherever electrical energy is available. Switching and protection devices should enable undisturbed working, allow complete utilization of motor and interrupt its operation only in cases when the motor is really endangered. One of such devices is the motor protection switch, in which functions of startup, switch-off, overload and short-circuit protection are combined. The paper deals with the analysis of heating of motor protection switch by permanent current load of 32 A. Joul losses are caused by that current and all parts of the switch are being heated as a result of heat transition from the site of production to the surrounding parts. Produced heat is partly used to increase the temperature of switch parts and partly conveyed into the surroundings. All three physical heat transition mechanisms perform at the transport of heat (Pic. 1). However, the influence of radiation was negligible because of low temperatures. Motor protection switch present a very complex 3D geometry, which has been simplyfied during the analysis. Parts of the switch i.e. are control device, mechanism, do not influence the temperature field and for that reason their presence has been neglected. The main source of heat consists of a heating coil with bimetal, so the influence of coil has been neglected, which has slighty changed the current flow of motor protection switch (Pic. 2). Three-pole constructions with partition walls are usually located between the individual poles. Treatment has been reduced to one pole with a suitable boundary condition i.e. heat isolation of partition wall between two poles. The final model of motor protection switch is presented in figure 3. Program package ANSYS, which is based on finite element method (FEM), was used for static calculation of temperature field. The results of calculations for two different values of convection coefficients on housing of motor protection switch were presented as that boundary condition, which has the most important influence on temperature field distribution. Convection coefficient at the conductor isolation was the same in the both cases. Temperature field distribution with a convection coefficient of 15 W/m2K is presented in figures 5 and 6. When a convection coefficient increases to 20 W/m2K temperature field distribution is presented in figures 7 and 8. As seen there, the temperature on housing of motor protection switch never exceeds the maximum heat permitted by a standard. Contact part on the bimetal and heating coil side is more strained by temperature as those two elements present the most important source of heat. Maximum temperature of the conductible part is the middle turns of the heating coil, which is caused by taking away the heat from both sides of the heating coil to the connected parts of the switch.
Keywords: stikala; temperaturno polje